Effects of the 4th industrial revolution on civil engineering with special emphasis on structural engineering – the case of Germany - Yaman, Tuğçe Sevil (Wpływ czwartej rewolucji przemysłowej na inżynierię lądową ze specjalnym naciskiem na inżynierię budowlaną – przypadek Niemiec, 2018)
The 4th Industrial Revolution (Industry 4.0) was introduced in 2011 by Germany. Internationally, it stands for the digitization of industry. It was developed as a future project within the framework of the high-tech strategy. Germany has the opportunity to play an active role in shaping the 4th Industrial Revolution. To do so, new business models and considerable potential for optimization of production and logistics can be tapped. Digital technologies have also widely found their way into civil engineering. The object of the study was to investigate elaborately Industry 4.0, mainly by focusing on the state of digitization in civil engineering field. The developments in civil engineering area in Germany, especially in structural engineering, as a result of the challenging project Industry 4.0 which is characterized by strong individualization of products under conditions of highly flexible production were examined in this study. Potentials of digitization, digitization in construction sector, challenges of digitization were also discussed. Consequently, derived conclusions were reported
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2018, Nr 2 (29), s. 56-77
Keywords: digital technologies; 4th industrial revolution; customized production; structural engineering; technologie cyfryzacji; czwarta rewolucja przemysłowa; produkcja przemysłowa; produkcja jednostkowa; inżynieria budowlana